DIGITALISASI PEMBAYARAN ZAKAT, INFAK DAN SEDEKAH (ZIS) (STUDI KASUS LAZISMU KOTA TASIKMALAYA) - Kusumah, Danial; Hanan Nur Syam Bilad (LPPM IAIT, 2023)
The purpose of thisstudy is to analyze the implementation and role of digital technology in collecting zakat, infaq and alms (ZIS) funds at LAZISMU Tasikmalaya City. The research method was carried out with a descriptive qualitative approach. the data sources used were primary and secondary data, the data collection methods used were interviews and documentation. The results of thisstudy indicate that: the form of implementation of the digitalization of collecting zakat, infaq and alms funds is digital payment and digital socialization by utilizing social media. Digitalization in the collection of zakat, infaq and alms funds plays a role because it makes it easier for LAZISMU and muzakki to save time and money. And also makes the collection of zakat funds more transparent, massive, effective and efficient. However, the role of digitalization has not been maximized due to the lack of human resources and the lack of promotion in the form of advertisements so that public knowledge of this digital system is very minimal and people are not yet literate in digital technology.